Evaluating interdisciplinary breastfeeding and lactation knowledge, attitudes and skills: An evaluation of a professional graduate programme for healthcare professionals. - Denise McGuinness; Kate Frazer; Karl F Conyard; Paula Cornally; Lauren Cooper; Niamh Vickers (PLoS ONE)
Breastfeeding theoretical and skills training is important for health care professionals engaging with the mother infant dyad to increase breastfeeding exclusivity and duration. The aim of this study was to evaluate the knowledge, attitudes and practices (KAPs) of health care professionals following completion of a university professional graduate programme in breastfeeding and lactation. A pre and post-educational study design was used. All students enrolled in a six month programme were invited to complete an online anonymous survey at two time points: January 2023 and July 2023. Ethical approval (LS-C-23-17) was obtained in January 2023. Descriptive statistics were utilised to report percentages and means, and independent T tests were used to report mean differences between variables on knowledge, attitude and practices. All students completed the module. The pre survey participant response rate was n = 55 (92.82%) and the post survey participant response rate n = 33 (60%). Comparison of the pre and post questionnaire report nine statistically significant results following completion of the university breastfeeding and lactation programme. Knowledge scores increased specifically with higher mean knowledge scores for reporting "I am confident with my knowledge about breastfeeding" and statistically significant mean difference of 0.29 following completion of the module (95% CI, 0.13 to 0.45) (t (64) = 3.59, p = 0.001). The programme evaluation identifies the importance of a professional graduate breastfeeding and lactation education programme for interdisciplinary health care professionals increasing knowledge, attitudes and practices and ultimately increasing breastfeeding rates in the short and long term, with improved maternal and child health outcomes.